Aguaçu : corporificação da travessia eco-endo-ontológica educativo-cultural em ciranda de saber-fazeres sob os cuidadosos olhares de resistências ancestrais - Oliveira, Maria Aparecida Hungria de Almeida (2023)
The memories of aboriginal and black-indigenous people of traditional communities throughout history have faced with invisibility and silencing in the academic fields, disregarding their strengths, as well as their resistance and embodied knowledge in their cultural experiences. The purpose of this research is to reveal the educational experiences embodied by the residents of the Aguaçu district, a traditional community located in the municipality of Cuiabá (MT). The investigative problem that requires an answer is to understand how the community manages and lives in harmony with nature, in each moment, with the singular body of each individuals, in a territory marked by various mutations. MerleauPontys phenomenology serves as the methodological framework for this study. We present the community’s experiences through the ethnographic method of dense description by Geertz (1978), mediated by a Freirean liberating education perspective, which proposes conversations with the permanent residents of the community under study and the teachers, through unique visits. As sources of information generation about the community's educational practices, audio recordings, photographic records, recordings and notes in field notebooks, and forms of artistic expressions, personal or collective, that sustain meanings for a phenomenologicalethnographic study were used. Among some of the results obtained, we can highlight that the community is at risk of losing this ancestral knowledge systems, among the guardians interviewed there’s a concern about the lack of continuity of this know-how among the younger generation. The teachers, despite facing numerous challenges in the context of a school in the countryside, are striving to chart a new path that promotes the value of local identities and knowledge. They recognize the need for greater collaboration between the school and the local community, and are working towards a more integrated approach. The 2021 PoliticalPedagogical Project, under construction, needs to meet the specificities of rural school like the one in Aguaçu. However, some projects that are being implemented, such as “Riches of my Aguaçu community” and “Routes”, are providing the opportunity to create transdisciplinary activities in school focused on the community’s environmental, cultural and economic reality. In light of all the above, with the actions or tactics associated with activities of a unique culture that highlight the diversity of meanings constructed and symbolized by traditional and religious knowledge, the community demonstrates the close relationship between school education, daily life, and their significance, highlighting how both forms of education can be integrated into everyday culture to pursue a more dignified way of life.